Faktor-Faktor yang Mempengaruhi Pinjaman Luar Negeri serta Imbasnya terhadap APBN - Samsubar Saleh (Unisia, 2008)
The research and study cover a theoretical discussion and empirical study on factorsaffecting the Indonesian Government’s foreign debt and their impact on the State Revenuesand Expenditures Budget (APBN) based on annual data from 1970 to 2008. Theresearch employs the Error Correction Model (ECM) approach by applying the OrdinaryLeast Square (OLS) method. The research results indicate that within a long-term period,there was a balance between changes in the Indonesian Government’s foreign debts andmacro-economic variables, i.e. budget deficit, exchange rate, export, GNP level, and dummyvariables for the 1997 economic crisis, despite the fact that the budget deficit variable didnot significantly affect the Indonesian Government’s foreign debts within the observedperiod. On the other hand, within a short-term period changes in the Indonesian Government’sforeign debts were affected significantly by dummy variables for the 1997 economic crisisand the ECT variable. Within such a period, the budget deficit, exchange rate, export, andGNP level variables did not significantly affect by the Indonesian Government’s foreigndebts. Thus, it could be concluded that the Indonesian Government’s foreign debts tendedto respond to changes occurring in macro-economic variables, especially export, exchangerate, economic growth, and condition of foreign debts post-1997 economic crisis.Keywords: foreign debt, budget, balance, macro-economic.